Assessing the Impact of the COVID-19 Pandemic on the Saudi Stock Market’s Performance and Sustainability - Yusuf, Nadia; Ali, Inass Salamah (European Journal of Sustainable Development, 2023)
The research investigates the immediate impact of the COVID-19 pandemic on the Saudi Stock Exchange (Tadawul) by analyzing the Tadawul All Share Index (TASI). Relying on a robust quantitative methodology, the study involved de-seasonalizing daily TASI 'Close' values using a 7-day moving average and employing ARIMA modeling to examine time-series characteristics for periods before and after the first reported case of COVID-19 in Saudi Arabia on March 2, 2020. The study spanned 115 days, with 56 days before and 59 days after the outbreak, resulting in a total of 115 observations. Advanced statistical tests, including a two-sample t-test and effect size calculation (Cohen's d), were conducted to statistically validate the differences in market performance. The findings revealed a significant decrease in TASI performance post-COVID-19, with increased market volatility. This data aligns with global observations of market disruptions during the pandemic and contributes to the understanding of crisis-induced market behaviors. Finally, the obtained results offer valuable insights into the complexities of stock market responses to global health emergencies while further underscoring the importance of considering external factors in market dynamics. Keywords: Stock market; COVID-19; financial market; performance; Tadawul; mortality; Saudi Arabia